The Influence Of Competency, Communication And Work Environment On Employee Performance In Mina Store - Bujana, Adhetia Teddy; Soejoko, Dodi Kusuma Hadi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purposse of this case is analize influence of competence, communication, work envirunmenntt on the performance of mina store employees Design/Methode/Approach : Used quantitative approach tachniqu used by casuality. The population is 30 employee Mina store Research Finding :The differennce from thiscase is that partially environment variables have a significannt effectt on employee performannce but variables competency work environment do not have a significannt effect on emplloyee performannce. Simultan, the variable of competency,communinication, work environnment has significant effect on employees mina store Theoretical contribution/Originality :There have not been many studies that have examined the influennce of comppetence,comuunication and work environnment on performance wealthy people Practitionel/Policy implication : Can be used for human Resources development at mina store Research limitation : Limitation this case delay in resources the research respondent